Phylogenies and traits provide distinct insights about the historical and contemporary assembly of aquatic insect communities - Saito, Victor S.; Cianciaruso, Marcus Vinicius; Siqueira, Tadeu [UNESP]; Fonseca-Gessner, Alaide A.; Pavoine, Sandrine (Wiley, 2016)
The assumption that traits and phylogenies can be used as proxies of species niche has faced criticisms. Evidence suggested that phylogenic relatedness is a weak proxy of trait similarity. Moreover, different processes can select different traits, giving opposing signals in null model analyses. To circumvent these criticisms, we separated traits of stream insects based on the concept of α and β niches, which should give clues about assembling pressures expected to act independently of each other. We investigated the congruence between the phylogenetic structure and trait structure of communities using all available traits and all possible combinations of traits (4095 combinations). To account for hierarchical assembling processes, we analyzed patterns on two spatial scales with three pools of genera. Beta niche traits selected a priori - i.e., traits related to environmental variation (e.g., respiration type) - were consistently clustered on the smaller scale, suggesting environmental filtering, while α niche traits - i.e., traits related to resource use (e.g., trophic position) - did not display the expected overdispersion, suggesting a weak role of competition. Using all traits together provided random patterns and the analysis of all possible combinations of traits provided scenarios ranging from strong clustering to overdispersion. Communities were phylogenetically overdispersed, a pattern previously interpreted as phylogenetic limiting similarity. However, our results likely reflect the co-occurrence of ancient clades due to the stability of stream habitats along the evolutionary scale. We advise ecologists to avoid using combinations of all available traits but rather carefully traits based on the objective under consideration. Both trait and phylogenetic approaches should be kept in the ecologist toolbox, but phylogenetic distances should not be used as proxies of traits differences. Although the phylogenetic structure revealed processes operating at the evolutionary scale, only specific traits explained local processes operating in our communities.
Keywords: Assembly rules; Community assembly; Ecophylogenetics; Habitat filtering; Niche complementarity; Trait structure